Penggunaan Model Problem Based Learning (PBL) untuk Meningkatkan Hasil Belajar Siswa - Mainake, Patresya Nova; Laamena, Christina M.; Gaspersz, Magy (Edumatica : Jurnal Pendidikan Matematika, 2021)
The ability of students to understand the material on the Three Variable Linear Equation System (SPLTV) is still an important problem that must be solved. Teachers as educators need to use various learning models to improve student learning outcomes. This study aims to determine the increase in student learning outcomes of class X SMAN 6 Ambon who are taught using the Problem Based Learning (PBL) model on SPLTV material. The type of research used is classroom action research (CAR) which consists of 2 cycles and each cycle consists of 2 meetings. The data sources are teachers and students of class X-IPA1 SMAN 6 Ambon in the 2019/2020 academic year while the research subjects are 25 students. The research instrument used is the SPLTV learning outcome test which has been validated by experts. To collect data, researchers used test and observation techniques.Â  The results showed that there was an increase in student learning outcomes. In the first cycle, only 13 students completed (44%) but in the second cycle the number of students who completed increased to 19 students (76%). Based on the completeness in cycle I and cycle II, there was an increase from cycle I to cycle II by 32%.